A formação de professores no Brasil: histórico e desdobramentos - Castro, Luciana Paula Vieira; Malacarne, Vilmar; Strieder, Dulce Maria (Revista Brasileira de Educação em Ciências e Educação Matemática, 2018)
Resumo: A formação de professores tem registros em todo o Planeta desde seu início em meados do século XI, a fim de amparar as práticas dos profissionais que atuavam em instituições de ensino à época. Tendo em vista a importância da história da educação para compreensão da realidade educacional atual, neste texto, via pesquisa bibliográfica, serão apontados aspectos da formação de professores a partir da análise do contexto histórico e atual no campo educacional e social. Atualmente, em termos legais, a prioridade empleitear a docência no Brasil, na Educação Básica, nos níveis Fundamental e Médio, é para profissionais graduados em cursos de Pedagogia e Licenciaturas. Em um panorama de constantes mudanças no campo educacional, atualmente, ser professor distingue-se de períodos anteriores, distinção essa, muitas vezes, não assistida no contexto da formação docente. Apesar de terem ocorrido alterações na formação dos professores no país, ainda há a necessidade de repensar sua estrutura, de maiores investimentos governamentais e reconhecimento social para que a formação e a atuação docente sejam mais efetivas. Palavras-chave: História da educação; Formação de professores; Políticas de formação de professores. Teachers’ training in Brazil: history and its results Abstract: The teachers training has been recorded throughout the Planet from its beginning in the middle of the eleventh centuryto support the professionals’ practices in educational institutions at the time. It should be highlighted the importance of the history of education to perceive the current educational reality, in this text, based on bibliographic research. So, some aspects of teachers’ training will be pointed out to analyze the historical and current context in educational and social field. Currently, according to the legal terms, the priority to apply for teaching in Brazil, in Basic Education, at elementary and Middle school levels, is for professionals who are graduated in Pedagogy and Undergraduate courses. According to a scenario of constant changes in educational field, today, there is a distinction to be a teacher nowadays when compared to the previous periods. Such distinction has not been often assisted in the teacher’s trainingcontext. Although there have been changes in teacher’s training in Brazil, there is still a need to rethink its structure, as well as greater government investments and social recognition so that training and teaching activities can be more effective. Keywords: History of education; Teacher’s training; Teacher’s training policies.